Enzymatic Potential of Native Fungal Strains of Agave Residues - Contreras Hernández, Maria Gorety; Aréchiga Carvajal, Elva Teresa; Moreno Jiménez, Martha Rocio; González Herrera, Silvia Marina; López Miranda, Javier; Prado Barrágan, Lilia Arely; Rutiaga Quiñones, Olga Miriam (2017)
Abstract. Orexins or hypocretins are neurotransmitters produced by a small population of neurons in the lateral hypothalamus. This family of peptides modulates sleep-wake cycle, arousal and feeding behaviors; however, the mechanisms regulating their expression remain to be fully elucidated. There is an interest in defining the key molecular elements in orexin regulation, as these may serve to identify targets for generating novel therapies for sleep disorders, obesity and addiction. Our previous studies showed that the expression of orexin was decreased in mice carrying null-mutations of the transcription factor early B-cell factor 2 (ebf2) and that the promoter region of the prepro-orexin (Hcrt) gene contained two putative ebf-binding sites, termed olf‑1 sites. In the present study, a minimal promoter region of the murine Hcrt gene was identified, which was able to drive the expression of a luciferase reporter gene in the human 293 cell line. Deletion of the olf1-site proximal to the transcription start site of the Hcrt gene increased reporter gene expression, whereas deletion of the distal olf1-like site decreased its expression. The lentiviral transduction of murine transcription factor ebf2 cDNA into 293 cells increased the gene expression driven by this minimal Hcrt-gene promoter and an electrophoretic mobility shift assays demonstrated that the distal olf1-like sequence was a binding site for ebf2.